Calculation of Losses from Rainfall Falling in the Design of Culverts and Drainage Systems on Highways - YULIN, He; BIELIATYNSKYI, Andrii O.; SYTNICHENKO, Nikolaj V.; BORODINA, Natalia A. (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
The article studies the problem of calculating the loss of atmospheric precipitation to the earth surface in the design of culverts and drainage systems of objects on highways. The analysis of current research revealed that existing expressions for determining infiltration do not currently fully take into account the physical processes that occur during each phase during the development infiltration. Therefore, the purpose of this work is to develop a more physically justified expression to determine the loss of rain run off considering each phase of water infiltration into the soil. To account for the initial losses in runoff due, it is proposed to use an index level of soil moisture, which takes into account the type of soil and the initial level of moisture. An equation for calculating the rain lost through runoff from rainfall and soil type that takes into account the land use and the initial moisture level is developed. The validation of the proposed equation shows that it can be used to determine the flow losses in the design of drainage systems on highways.